Haloalkane dehalogenases: biotechnological applications - Koudelakova, Tana; Bidmanova, Sarka; Dvorak, Pavel; Pavelka, Antonin; Chaloupkova, Radka; Prokop, Zbynek; Damborsky, Jiri (Biotechnology journal, 2013)
Haloalkane dehalogenases (EC 3.8.1.5, HLDs) are α/β-hydrolases which act to cleave carbon-halogen bonds. Due to their unique catalytic mechanism, broad substrate specificity and high robustness, the members of this enzyme family have been employed in several practical applications: (i) biocatalytic preparation of optically pure building-blocks for organic synthesis; (ii) recycling of by-products from chemical processes; (iii) bioremediation of toxic environmental pollutants; (iv) decontamination of warfare agents; (v) biosensing of environmental pollutants; and (vi) protein tagging for cell imaging and protein analysis. This review discusses the application of HLDs in the context of the biochemical properties of individual enzymes. Further extension of HLD uses within the field of biotechnology will require currently limiting factors - such as low expression, product inhibition, insufficient enzyme selectivity, low affinity and catalytic efficiency towards selected substrates, and instability in the presence of organic co-solvents - to be overcome. We propose that strategies based on protein engineering and isolation of novel HLDs from extremophilic microorganisms may offer solutions.
Keywords: Animals; Hydrolases; lidé; Humans; Biotechnology; zvířata; hydrolasy; biotechnologie